Glanzmann′s thrombasthenia associated with HBsAg-positive child: A case report - Poornima G; Shivaprasad S; Ashok L (Wolters Kluwer Medknow Publications, 2007)
Glanzmann′s thrombasthenia is a rare hemorrhagic disorder characterized by prolonged bleeding time and diminished clot retraction. The disease is marked by frequent mucocutaneous hemorrhage which is mainly due to qualitative defects of platelets. A case of a 14-year-old HBsAg-positive adolescent male with Glanzmann′s thrombasthenia has been presented.